Perceptual Analysis of Diverse Perspectives and Desired Proficiencies in 21st-Century Skills Among College-Going Students - Namita, Namita; Lalita Vatta (Indian Journal of Extension Education, 2025)
In the dynamic post-secondarylearning environment, understanding the multifaceted perspectives and sought-after competencies in 21st-century skills among college students is paramount. The ascendancy of 21st-century skills, encompassing learning and innovation skills, information and media literacy, as well as life and career skills, has become pronounced due to the widespread adoption of online education, driven by recent global circumstances. Thepresent study undertakes a perception analysis of 21st-century skills among undergraduates enrolled in traditional courses at Banaras Hindu University (BHU), Varanasifrom2023-2024. Sample size of 325 participants was surveyed through a self- structuredtool.The results revealed consistent familiarity with the term “21st-century skills” among students, regardless of gender, course section, or other demographic factors.There was insufficient evidence of an association between familiarity with the term ‘21st-century skills’ and related factors. Students did not vary notably in their assessment of the importance of these skills across course sections.About abilities like critical thinking, creativity, and leadership, there were notable differences in perceptions.